A Cooling System for a Mushroom House for Use in the Upper Central Region Climate of Thailand - Chantana, Chanamon (Naresuan University Journal: Science and Technology (NUJST); Vol 27 No 3 (2019): July-September 2019DO - 10.14456/nujst.2019.22, 2019)
This study investigated a cooling system for mushroom cultivation for both experimental and theoretical purposes. The system was used in shitake mushroom cultivation in the upper central region climate of Thailand in winter. The system consisted of a night cooling system, a cooling coil and direct evaporative pad cooling.  The night cooling system was set up and tested from November to December 2017. The COP equation for the system was correlated with experimental data and then used to predict cold water tank temperature. It was found that the cold water tank temperature was 25.50 °C, while the average dry bulb day time temperature and wet bulb night time temperatures were 31 °C and 25.72 °C respectively. The outlet air temperature from the whole system was then estimated from the cold water tank temperature. The resulting outlet air temperature was cooled to 22.04 °C. Thus, the system could satisfy the criteria temperature for the air temperature inside the mushroom house which was defined at 28 °C. Nomenclature A                      heat transfer area, m 2 C p                       specific heat, kJ kg -1 K -1 COP                   coefficient of performance m                      mass , kg RH                    relative humidity T                      temperature, °C U                      overall heat transfer coefficient, W m -2 K -1 Subscript ci                      cold fluid inlet db                      dry bulb hi                      hot fluid inlet w                      water wb                     wet bulb Keywords : Cooling, Mushroom, Greenhouse